EVALUASI PENERAPAN AKUNTANSI ATAS ASET TETAP (KONTAINER) PADA PT MERATUS LINE CABANG BITUNG - Helen, Rumayar Angela Natesha; Saerang, David Paul Elia; Pangerapan, Sonny (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Fixed assets are the most instrumental in supporting the operational activities of the company, fixed assets are used to run the business operations of the company to produce goods or services. Therefore, it is necessary to apply a fixed asset accounting to avoid the occurrence of errors that will affect the financial statements for financial statement information will impact as a decision-making material. The purpose of this research is to know the company's policy regarding the application of fixed asset accounting based on Statement of Financial Accounting Standards. The analytical method used by the author is descriptive analysis with qualitative approach, using direct interview technique, documentation and email. From the results of the study can be concluded that the company run accounting activities guided by accounting policies that have led to Statement of Financial Accounting Standards about fixed assets.Keywords : Fixed Assets, Statement of Financial Accounting Standards